Exploratory Study of Physical Environment Factors Affecting Tuberculosis Endemics Houses in Kebumen District, Indonesia - Anggana Fitri Satwikasari (International Journal of Built Environment and Scientific Research, 2018)
According to prior researchs, the bacteria of Tuberculosis can spreads easily in an unhealthy environment influenced by several physical environment factors in a house. In Kebumen, where mostly classified as rural area, there are 3 sub-districts that is stated to be the most endemic area with hundreds of TB cases detected every year. By selecting 50 patients from ‘Balai Pengobatan Paru-paru’ (BP4)’s medical record, some physical assessments have been done on some indicators such as Residential Density, Ventilation system, Daylighting System, Temperature, Humidity, and also Material Quality. This quantitative research collected the existing physical variables through close-ended questionnaire and field measurements. Those data were later analyzed with distribution method by using digital data analysis software named JMP and compared them with the prevailing standard values. The result showed that eventhough all of 50 respondents have ideal Residential Density Percentage, their Ventilation and Daylighting System didn’t conforming with the standard. Those houses also have high Humidity ( > 60%) and high Temperature ( >300 C) that may be caused by the poor air circulation system inside the house. However, almost all of the infected houses were found to use brick as their wall material with various quality and used ceramics or ram earth as their floor material.